Qualidade de vida dos estudantes de medicina e seus determinantes - LIMA, Ana Carolina Araujo (2023)
The objective of the study was to characterize the quality of life (QoL) of medical students, as well as to relate it to sociodemographic characteristics and the way students access the institution. It was carried out in an observational, crosssectional study, with data collection from the selfapplication of the World Health Organization Questionnaire for Quality of Life Brief Form (WHOQOLbref). A total of 205 undergraduate medical students from the Universidade Federal do Pará participated in the research. The mean age was 23.7 years, most subjects were female (52%) and the predominant selfdeclared color was brown (45%). The majority reported access due to wide competition (61%) and there was a predominance of declared income between 410 minimum wages (37%). In the multivariate analysis, it was found that income, access mode and year of course were correlated with QoL scores. The results obtained make it possible to create strategies for care aimed at the most vulnerable students during graduation, especially those with variables that negatively influence QoL scores.